Investigation of In Vitro Effects of Paracetamol on Contractions of Jejunum and Ileum Smooth Muscles in Dioestrus Female Rats - Bozyil, Ahmed Sait; Kacar, Emine; Sayin, Orhan; Pervin, Mehtap; Oz, Zeynep Dila; Hekim, Munevver Gizem; Serhatlioglu, Ihsan (Wiley, 2023)
[Abstract Not Available]
Keywords: Ileum; Isometric contration; Jejunum; Paracetamol; Rat